Evidence of survival bias in the association between APOE-Є4 and age at ischemic stroke onset - von Berg, Joanna; McArdle, Patrick F.; Häppölä, Paavo; Haessler, Jeffrey; Kooperberg, Charles; Lemmens, Robin; Pezzini, Alessandro; Thijs, Vincent; Pulit, Sara L.; Kittner, Steven J.; Mitchell, Braxton D.; de Ridder, Jeroen; et al. (Frontiers in Genetics, 2024)
Utilizing a case-only genome-wide association study (GWAS) design we identified a significant association between the APOE locus, specifically the rs429358 variant, and age at onset (AAO) of ischemic stroke. This exonic variant in APOE, linked to the APOE-Є4 allele, exhibited a compelling correlation, with each copy of the allele associated with a 1.29 years earlier stroke onset. Notably, our findings, supported by a robust discovery cohort of 10,857 ischemic stroke cases and reinforced through meta-analysis with replication cohorts, shed light on a potential survival bias influencing AAO. While APOE-Є4 has previously been linked to increased mortality and stroke AAO, our simulation study suggests that this association may be independent of ischemic stroke itself, emphasizing the need for nuanced interpretation in understanding the genetic factors influencing age at onset in stroke cases.